Immune Checkpoint in Glioblastoma: Promising and Challenging - Huang, Jing; Liu, Fangkun; Liu, Zhixiong; Tang, Hui; Wu, Haishan; Gong, Qianni; Chen, Jindong (Frontiers in Pharmacology, 2017)
Glioblastoma (GBM) is a severe malignant brain cancer with poor overall survival. Conventional intervention remains dismal to prevent recurrence and deterioration of GBM cell. Recent years have witnessed exciting breakthroughs in novel immune strategies, especially checkpoint inhibitors, some of which have becoming adjuvant setting after standard of care in melanoma. Several clinical trials of checkpoint inhibitors are ongoing in glioblastoma and other brain carcinomas. Plus, synergistic combinations of checkpoint inhibitors with conventional therapy strategies—radiotherapy, temozolomide, bevacizumab and corticosteroids are now exploited and applied in clinical settings. This review highlights the recent developments of checkpoint in GBM immunotherapy to provide a brief and comprehensive review of current treatment options. Furthermore, we will discuss challenges remained, such as unique immune system of central nervous system (CNS), immune-related toxicities, synergies and adverse interactions of combination therapies.